2022
DOI: 10.1158/1078-0432.ccr-21-3078
|View full text |Cite
|
Sign up to set email alerts
|

Initial Phase I Safety Study of Gedatolisib plus Cofetuzumab Pelidotin for Patients with Metastatic Triple-Negative Breast Cancer

Abstract: Purpose: The PI3K pathway is dysregulated in the majority of triple-negative breast cancer(TNBCs), yet single agent inhibition of PI3K has been ineffective in TNBC. PI3K inhibition leads to an immediate compensatory up-regulation of the Wnt pathway. Dual targeting of both pathways is highly synergistic against TNBC models in vitro and in vivo. We initiated a Phase I clinical trial combining gedatolisib, a pan-class I isoform PI3K/mTOR inhibitor, and cofetuzumab pelidotin, an antibody-drug conjugate against the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, gedatolisib can enhance radio and chemosensitivity by inhibiting the PI3K/AKT/mTOR pathways to decrease DNA damage repair mechanisms [ 106 ]. Recently, an investigation reported that combining PKI-587 with Cofetuzumab Pelidotin, a protein tyrosine kinase 7 (PTK7)-targeted, auristatin-based antibody-drug conjugate in patients with metastatic triple-negative breast cancer (TNBC) was associated with promising clinical activity, two months median PFS, and moderate toxicity (anorexia nausea, mucositis, and fatigue) [ 107 ]. PKI-587 can increase radiosensitization.…”
Section: Dual Pathway Inhibitorsmentioning
confidence: 99%
“…Moreover, gedatolisib can enhance radio and chemosensitivity by inhibiting the PI3K/AKT/mTOR pathways to decrease DNA damage repair mechanisms [ 106 ]. Recently, an investigation reported that combining PKI-587 with Cofetuzumab Pelidotin, a protein tyrosine kinase 7 (PTK7)-targeted, auristatin-based antibody-drug conjugate in patients with metastatic triple-negative breast cancer (TNBC) was associated with promising clinical activity, two months median PFS, and moderate toxicity (anorexia nausea, mucositis, and fatigue) [ 107 ]. PKI-587 can increase radiosensitization.…”
Section: Dual Pathway Inhibitorsmentioning
confidence: 99%
“…Cofetuzumab pelidotin (PTK7 inhibitor) enhanced anti-tumor effects of gedatolisib in phase I trials of individuals with ER − breast cancer [ 113 ].…”
Section: Pi3k Signaling Enhances Wnt/β-catenin Activation In Er ...mentioning
confidence: 99%
“…Similar effects have been observed in other cancers such as pancreatic cancer, where combined ETC-159 (PORCN inhibitor) and pictilisib treatment synergistically reduced pancreatic cancer cell proliferation and xenograft tumor growth [ 112 ]. Recently, phase I clinical trials were conducted in individuals with metastatic ER − breast cancer using the dual PI3Kα/γ and mTOR inhibitor, gedatolisib, in combination with cofetuzumab pelidotin, an antibody–drug conjugate with an auristatin payload targeting the Wnt co-receptor, protein tyrosine kinase 7 (PTK7) [ 113 ]. This PI3K/Wnt combination therapy had manageable toxicity, and some individuals exhibited a partial clinical response with disease stabilization [ 113 ].…”
Section: Pi3k Signaling Suppresses Wnt/β-catenin Activation In Er ...mentioning
confidence: 99%
See 1 more Smart Citation
“…PIK3CA mutations caused by activation of the WNT/β-catenin signaling pathway may decrease colorectal cancer cell sensitivity to the dual PI3K/mTOR inhibitor PKI-587 [ 176 ]. PKI-587 plus cofetuzumab pelidotin in metastatic triple-negative breast cancer (TNBC) showed moderate toxicity and promising clinical activity [ 177 ]. PKI-587 combined with carboplatin and paclitaxel in clear cell ovarian cancer exhibited similar trends [ 178 ].…”
Section: Inhibitors Of the Pi3k/akt/mtor Pathwaymentioning
confidence: 99%